2023
DOI: 10.25270/wnds/22094
|View full text |Cite
|
Sign up to set email alerts
|

Final Efficacy and Cost Analysis of a Fish Skin Graft vs Standard of Care in the Management of Chronic Diabetic Foot Ulcers: A Prospective, Multicenter, Randomized Controlled Clinical Trial

Abstract: Introduction. DFUs remain a cause of significant morbidity. Objective. This is the third of 3 planned articles reporting on a prospective, multicenter, randomized controlled trial evaluating the use of omega-3–rich acellular FSG compared with CAT in the management of DFUs. Materials and Methods. A total of 102 patients with a DFU (n = 51 FSG, n = 51 CAT) participated in the trial as ITT candidates, with 77 of those patients included in the PP analysis (n = 43 FSG, n = 34 CAT). Six months after treatment, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…When we reviewed the individual data, we noticed that the patients with the highest costs, and who were statistical outliers, had either larger wounds or very high BMI, (e.g., patients with wounds of 10 cm 2 or BMI of 45). This cost is still comparable to the values for either amniotic/placental tissue costs of $1771 to $2252USD 16,32 while it is lower than the $3019 that has been reported for porcine grafts 33 or the $4089 for Fish‐Skin grafts 34 . Considering the age of some of the publications that had provided cost information, the values are likely to be higher after adjusting for inflation.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…When we reviewed the individual data, we noticed that the patients with the highest costs, and who were statistical outliers, had either larger wounds or very high BMI, (e.g., patients with wounds of 10 cm 2 or BMI of 45). This cost is still comparable to the values for either amniotic/placental tissue costs of $1771 to $2252USD 16,32 while it is lower than the $3019 that has been reported for porcine grafts 33 or the $4089 for Fish‐Skin grafts 34 . Considering the age of some of the publications that had provided cost information, the values are likely to be higher after adjusting for inflation.…”
Section: Discussionsupporting
confidence: 50%
“…This cost is still comparable to the values for either amniotic/placental tissue costs of $1771 to $2252USD 16,32 while it is lower than the $3019 that has been reported for porcine grafts 33 or the $4089 for Fish-Skin grafts. 34 Considering the age of some of the publications that had provided cost information, the values are likely to be higher after adjusting for inflation.…”
Section: Derma-gidementioning
confidence: 99%
“…However, one randomized-controlled trial comparing iFSGs versus the standard of care (SOC) in diabetic foot ulcers was recently published, while others are ongoing [ 20 , 21 , 22 , 47 ]. The multi-center RCT by Lantis and colleagues involving 102 patients has shown superior wound healing rates and wound area reduction over the SOC for diabetic foot ulcers treated with iFSGs ( p = 0.0163) at 12 weeks [ 47 ]. The results of the European Horizon-funded multi-national, multi-center RCT (Odin trial; H2020-EU.3.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The high cost of iFSGs may be another limiting limiting factor known for other tissue-based therapies tissue-based therapies, especially in resource-limited settings or areas with inadequate healthcare coverage. However, a recently published cost analysis comparing iFSGs versus the SOC using collagen alginate therapy in diabetic foot ulcers demonstrated a reduction of the overall annualized treatment cost due to faster wound healing [ 47 ]. This analysis might convince healthcare providers to cover the treatment costs and support using iFSGs in every healthcare region independent of the local socioeconomic situation.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Diabetic wounds healed in 71.4% of cases (the baseline mean size of the DFU retained in this study was 35.8 ± 30.6 cm 2 ( Table 3 )). Previous studies reported a 31.4% healing rate of DFU with saline (baseline ulcer size 1–25 cm 2 ) [ 23 ], 41.7% with a standard of care (4.7 ± 2.9 cm 2 at baseline) [ 24 ], or 73.7% with saline gauze (initial mean size 2.3 ± 2.7 cm 2 ) [ 25 ]. It is evident that the healing time of DFU depends on its size, and regarding that, HA+ KI 3 performed well.…”
Section: Discussionmentioning
confidence: 99%